The Value-Added of Internal Audit Function in Government of Indonesia - Elychia Roly Putri; Dodik Siswantoro (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to evaluate the value-added of the internal audit provided by Inspektorat Jenderal to Direktorat Jenderal X. The motivation of the research is due to research on the value-added is still needed, especially in the Indonesian government sector. Data collection techniques were carried out through questionnaires, interviews, and documents relevant to the research. The data analysis was carried out by referring to the conceptual framework to measure the value-added of internal audit. The results of this study indicate that the internal audit activities of Inspektorat Jenderal have contributed to providing value-added for Direktorat Jenderal X. The creation of value-added provided by Inspektorat Jenderal is influenced by the evaluation of the effectiveness of Governance, Risk Management, and Internal Control (GRC) at Direktorat Jenderal X and the effectiveness of internal audit activities.